Does Fraud Pentagon cause financial report manipulation? - Ellen Crisna; Prima Appriwenni (Jurnal Ekonomi Perusahaan, 2021)
The most visible measure of a company's health is its financial reports. This critical function may motivate management to engage in fraudulent activities to impress that the company is constantly in good shape and profitable. As a result, the information is distorted and potentially jeopardizes investment decisions. Therefore, it is crucial to find a way to detect that deviant behavior. This research aims to fulfill this requirement. Using the period of 2017-2019 as the sample timeframe, the authors pay attention to the IDX30 version companies listed on the IDX. Financial statement fraud, financial stability, financial targets, industry type, poor supervision, auditor turnover, change of directors, and the frequency of appearance of CEO images are the variables under investigation. The secondary data from 48 units of analysis were analyzed using logistic regression. Financial stability and industry structure have a significant effect on financial statement fraud. Other variables under investigation have little effect. Original Article | Turnitin